Вплив єврорегіонів на транскордонне співробітництво сусідніх держав (на прикладі єврорегіону «Дністер») - Патлашинська, І. В.; Patlashynska, I.V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
The concept of "Euroregion" and the impact of the presence of European regions to improve cooperation between neighboring states are analyzed in this paper. The process of creating the youngest Euroregion of Ukraine "Dniester" is examed.
Impact of European regions at cross-border cooperation of neighboring countries (for example Euroregion "Dniester")
І. В. Патлашинська, асист. кафедри міжнародної інформації Східноєвропейського національного університету імені Лесі Українки (Україна, м.Луцьк)
Keywords: the European region; transborder cooperation; eurointegration